(untitled) (Journal of actual problems of jurisprudence, 2019)
The criminalistic peculiarities of trassologi objects are considered in this article necessary are also drawn. Basic objects of research of trasologii: statistical, dynamic. The general rules of finding, assertions and taking of tracks, are resulted. Strengthening of tracks is carried out description in protocol of consequence actions. A role and features of objects of trassologii was scalene examined in scientific criminalistics. Key words: trasologii, dynamic tracks, local tracks, peripheral tracks, static tracks.